2010
DOI: 10.1136/jme.2010.035485
|View full text |Cite
|
Sign up to set email alerts
|

What do our patients understand about their trial participation? Assessing patients' understanding of their informed consent consultation about randomised clinical trials

Abstract: This study fills an important empirical research gap of what is ethically demanded in an RCT consultation and what is really understood by patients. The qualitative approach enabled us to obtain new results about cancer patients' understanding of informed consent, to clarify patients' needs and to develop new ideas to optimise the informed consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 23 publications
(21 reference statements)
4
50
0
1
Order By: Relevance
“…More robust studies are needed to assess the effectiveness of training programmes, although these will need to give careful consideration to how ''successful'' interventions should be defined (ie, completion of study or evidence to support closure) and what the outcomes should be (ie, screening and eligibility counts, recruitment rates, or changes in informed consent). Furthermore, given that research has demonstrated that patients can find RCT concepts confusing [14][15][16][17], it is important not to neglect the patient's perspective of the recruitment process, and to further develop methods to facilitate joint decision making and ensure fully informed consent.…”
Section: Future Directions For Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…More robust studies are needed to assess the effectiveness of training programmes, although these will need to give careful consideration to how ''successful'' interventions should be defined (ie, completion of study or evidence to support closure) and what the outcomes should be (ie, screening and eligibility counts, recruitment rates, or changes in informed consent). Furthermore, given that research has demonstrated that patients can find RCT concepts confusing [14][15][16][17], it is important not to neglect the patient's perspective of the recruitment process, and to further develop methods to facilitate joint decision making and ensure fully informed consent.…”
Section: Future Directions For Researchmentioning
confidence: 99%
“…Although patient information leaflets are strictly regulated by ethics committees, the communication style of the recruiter (usually a clinician or nurse) plays an important role in patients' understanding of the information and their willingness to join the study [12]. Research has shown that information conveyed during recruitment appointments varies considerably in content and quality [13], and patients often have a poor understanding of RCT concepts [14][15][16][17]. A systematic review of interventions to improve the recruitment activity of clinicians reported that the most promising interventions were studies that used qualitative research to identify key issues and develop interventions to improve recruitment [18].…”
Section: Introductionmentioning
confidence: 99%
“…There is little in the literature to describe health professionals' attitudes to choice of venous access devices. Quantitative studies indicate that whilst factors such as cost, durability and ease of use for medical personnel all feature in device decision making, little or no consideration is given to participants' views or preferences (26,27). The need for more studies to investigate the issue of patient satisfaction and quality of life in relation to venous access devices has been highlighted (28).…”
Section: Methodsmentioning
confidence: 99%
“…In the context of research, this places a responsibility on investigators to provide potential participants full and accurate information and to ensure that their study processes promote individual participants' understanding and ability to choose freely (Behrendt, Gölz, Roesler, Bertz, & Wünsch, 2011). Researchers must take extra care when potential participants are subjected to compulsion in other aspects of their lives (Edens, Epstein, Stiles, & Poythress, 2011;Wolbransky, Goldstein, Giallella, & Heilbrun, 2013).…”
Section: Literature Regarding Informed Consent and The Context Of Thementioning
confidence: 99%
“…Obtaining consent that is fully informed and voluntary can be resource-intensive and, in some cases, problematic (Behrendt et al, 2011). There can also be various circumstances where seeking consent is impractical or impossible, such as in the delivery of emergency medical intervention (Appelbaum, Roth, & Lidz, 1982;Edwards et al, 2002;Mason & Allmark, 2000), or in the case of using stored data or materials after participants have left an institution (Tu et al, 2004).…”
Section: Literature Regarding Informed Consent and The Context Of Thementioning
confidence: 99%